BACKCHANNEL AS FORMATIVE ASSESSMENT IN ENGLISH CLASSROOM; THE STUDENTS’ PERSPECTIVE - Vara Dika Maharani; Entika Fani Prastikawa; Wiyaka (Journal of English Education and Linguistics, 2022)
Dealing with assessment, formative is one way of assessing students' performance during classroom activities. The latest curriculum in Indonesia, curriculum 2013, demands teachers to assess students not just at the end of learning. The objectives of the study are to find out students’ responses on the implementation of backchannel as formative assessment implemented in English classroom, to identify areas of students learning activity are influenced by backchannel implemented in English classroom, and to describe the difficulties faced by the students in the implementation of backchannel in their English classroom. The approach of this study was qualitative design. The subjects are the eighth-grade students of SMP N 6 Semarang. The results showed that the backchannel method was applied in eighth D class is success. The backchannel method as a formative assessment gets positive responses from students. The students are mostly affected in the area of backchannel in which they can improve their skills in English with a high understanding of the process. Some students can improve their speaking skills because they receive a lot of new vocabulary and this method makes them more active. The challenges that they faced are about time, understanding and internet signal.